The dragon who couldn't breathe fire : a book about being different ([Hong Kong] : Time Life Asia, 1997)
"A little dragon feels sad because he can't breathe fire like other dragons. He runs away from home in search of the secret of breathing fire. A friendly witch tries to help him with her magic spells, but somehow they never turn out quite right. In the end, the dragon finds out that being different can be fun."--Cover.
Keywords: Values -- Juvenile literature; Self-acceptance -- Juvenile literature